Direct and indirect effects of alexithymia on disordered eating in a non-clinical female sample: Determining the role of negative affect - Wallis, Deborah J.; Ridout, Nathan (Frontiers in Psychiatry, 2022)
Background Alexithymia is an independent predictor of symptoms of eating disorders, but also influences disordered eating in clinical samples indirectly via negative affect (depression and anxiety). The aim of the current work was to establish if alexithymia predicts disordered eating in a non-clinical sample directly and indirectly (via negative affect). Methods A sample of healthy females (n=248) completed measures of depression, anxiety, alexithymia, and disordered eating (drive for thinness, bulimia, and body dissatisfaction). Bias-corrected bootstrapping was used to conduct parallel mediation analyses to determine if negative affect (depression and anxiety) mediated the influence of alexithymia on disordered eating Results The relationship between alexithymia (difficulty identifying feelings) and drive for thinness was mediated by depression but not anxiety. The link between difficulty identifying feelings and bulimia was mediated by anxiety but not depression. The correlation between alexithymia (difficulty describing feelings) and body dissatisfaction was mediated by both depression and anxiety. However, after controlling for negative affect, difficulty identifying feelings remained an independent predictor of drive for thinness, and difficulty describing feelings remained an independent predictor of body dissatisfaction. Conclusions Facets of alexithymia (DIF and DDF) directly predict disordered eating in healthy participants as well as indirectly via depression and anxiety. These findings suggest that targeted interventions to improve the ability of individuals to identify and describe their feelings could be beneficial in reducing disordered eating, particularly in those ‘at risk’ of developing eating disorders.